2017
DOI: 10.1016/j.wjorl.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Publication trends in obstructive sleep apnea: Evidence of need for more evidence

Abstract: ObjectivePublished research in obstructive sleep apnea (OSA) appears limited despite OSA being a highly prevalent adult and pediatric disease leading to many adverse outcomes if left untreated. We aimed to quantify the deficit in OSA scientific literature in order to provide a novel way of identifying gaps in knowledge and a need for further research inquiry.MethodsThis was a Bibliometric analysis study. Using Ovid Medline database we analyzed and compared research output (medical and surgical) between adult O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Reliable and accurate prevalence estimates of PH in children with OSA will allow for improved resource allocation and health care planning. 34…”
Section: Introductionmentioning
confidence: 99%
“…Reliable and accurate prevalence estimates of PH in children with OSA will allow for improved resource allocation and health care planning. 34…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear what the clinical landscape of OSA research is at present. A recent publication by Araslanova et al demonstrated that adult OSA research publications are significantly underrepresented when compared to other chronic medical conditions such as coronary artery disease, diabetes mellitus, and osteoarthritis. OSA had significantly fewer randomized controlled trials and meta‐analyses when compared to these other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[28] In the pediatric population, the prevalence of OSA is between 1 and 6% in all children and 59% in obese children. [29] There is a high risk of perioperative complications. Among 111 pediatric tonsillectomy cases, 57% of children with death or near-death events met the criteria for being at risk for OSA, and apnea was observed in 46% of these patients.…”
Section: Research Areasmentioning
confidence: 99%